2021
DOI: 10.5624/isd.20210120
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic accuracy of imaging examinations for peri-implant bone defects around titanium and zirconium dioxide implants: A systematic review and meta-analysis

Abstract: Purpose This systematic review and meta-analysis assessed the diagnostic accuracy of imaging examinations for the detection of peri-implant bone defects and compared the diagnostic accuracy between titanium (Ti) and zirconium dioxide (ZrO 2 ) implants. Materials and Methods Six online databases were searched, and studies were selected based on eligibility criteria. The studies included in the systematic review underwent bias and applicability … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…Thus, the limitations of the CBCT systems and the amount of artifacts in these images should be considered. However, Chagas et al [ 27 ] found no significant difference regarding diagnostic accuracy between CBCT images of peri-implant bone defects around titanium implants and zirconium dioxide implants.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the limitations of the CBCT systems and the amount of artifacts in these images should be considered. However, Chagas et al [ 27 ] found no significant difference regarding diagnostic accuracy between CBCT images of peri-implant bone defects around titanium implants and zirconium dioxide implants.…”
Section: Discussionmentioning
confidence: 99%
“… 1 2 CBCT was first applied in the dental field in the mid-1990s, and the scope of its application has been gradually expanded. 3 4 5 According to a 2019 research report in South Korea, CBCT was used 778,766 times in 2019, compared to 399,327 times in 2016. 6 As the usage of CBCT in the dental field has increased dramatically, the importance of equipment management has also been recognized.…”
Section: Introductionmentioning
confidence: 99%